(untitled) (Journal of Shaheed Suhrawardy Medical College, 2022)
Background: Dexmedetomidine is a newer adjuvant anesthetic agent which is gaining its popularity day by day in our perspective. As an anaesthetic adjuvant dexmedetomidine has been shown to provide good perioperative haemodynamic stability during laparoscopic surgeries. But still it is to be judged its efficacy as adjuvant agent in our aspect. Objective: To observe the haemodynamic effects of intravenous dexmedetomidine during laparoscopic cholecystectomy. Methods: Eighty(80) patients (ASA grade l and ll) who underwent laparoscopic cholecystectomy surgery were randomly selected and were scrutinized according to eligibility criteria.The selected patients were divided into two groups on even and odd number basis. Even number Group A (n=40): received a bolus dose of I.V dexmedetomidine 1μg/kg over 10 minutes before induction of Anesthesia and then I.V infusion of 0.5 μg/kg/hr as a maintenance infusion and odd number Group B(n=40): received a bolus dose of same volume of normal saline before induction of Anesthesia and infusion was continued during surgery. General anesthesia was administered in all patients using fentanyl, thiopentone, succinylcholine, nitrous oxide in oxygen, halothane and muscle relaxation maintained with vecuronium bromide. A pre-tested, observation based, peer-reviewed data collection sheet was prepared before study. Results: Intra-operative mean Heart rate of Group B patients were more higher than those of Group A patients and showed statistically significant differences (P=0.003). Mean arterial pressure of Group B patients were far more higher than Group A patients in different events of peroperative period which is statistically significant (P=0.001). Mean diastolic blood pressure in Group B was significantly higher than that of Group A (P=0.0001). Conclusion: Dexmedetomidine is an effective drug that can be used as adjunctive infusion in general anesthesia in an intention to stable the hemodynamic profile in the peroperative period of different surgeries. Specially in laparoscopic cholecystectomy some patients with cardiac risk become vulnerable after CO2 gas in sufflation which can be properly managed using Dexmedetomidine. J Shaheed Suhrawardy Med Coll 2021; 13(1): 26-32